Parabrachial Neurons Promote Behavior and Electroencephalographic Arousal From General Anesthesia - Luo, Tianyuan; Yu, Shouyang; Cai, Shuang; Zhang, Yu; Jiao, Yingfu; Yu, Tian; Yu, Weifeng (Frontiers in Molecular Neuroscience, 2018)
General anesthesia has been utilized clinically for more than 170 years, yet its underlying mechanisms are still not fully understood. The parabrachial nucleus (PB) in the brainstem has been shown to be crucial for regulating wakefulness and signs of arousal on the cortical electroencephalogram (EEG). Lesions of PB complex lead to unresponsiveness and a monotonous high-voltage, slow-wave EEG, which are the two main features of general anesthesia. However, it is unclear whether and how the PB functions in the process of general anesthesia. By recording in vivo calcium levels in real-time, we found the PB neural activity is suppressed during anesthesia, while it is robustly activated during recovery from propofol and isoflurane anesthesia. Activation of PB neurons by “designer receptors exclusively activated by designer drugs” (DREADDs) shortened the recovery time but did not change the induction time. Cortical EEG recordings revealed that the PB neural activation specifically affected the recovery period with a decrease of δ-band power or an increase in β-band power; no EEG changes were seen in anesthesia period. Furthermore, PB activation elicited neural activation in the prefrontal cortex, basal forebrain, lateral hypothalamus, thalamus, and supramammillary nucleus. Thus, the PB is critical for behavioral and electroencephalographic arousal without affecting the induction of general anesthesia.